Advancements and Challenges in Biomaterials: Innovations, Sustainability, and Future Prospects - Erzen, Buket; Karatas, Mukaddes; Orhan, Ramazan; Aydogmus, Ercan (Taylor & Francis Inc, 2026)
Biomaterials have emerged as indispensable tools in modern medicine and biotechnology, driving innovations across diverse fields such as tissue engineering, orthopedic implants, drug delivery systems and wound healing. This review examines the design principles, classifications and advancements of biomaterials, emphasizing key properties like biocompatibility, biodegradability and mechanical functionality. The evolution of biomaterials from simple natural substances to sophisticated synthetic and hybrid materials highlights the impact of advancements in nanotechnology, 3D printing and biomimetic approaches. These technologies have enabled the development of patient-specific implants, scaffolds and advanced drug delivery systems, significantly enhancing healthcare outcomes. Despite these achievements, challenges such as high production costs, regulatory barriers and long-term safety validation remain critical hurdles for the widespread adoption of biomaterials. Furthermore, ethical considerations related to genetic engineering and sustainability must be integrated into development processes. Sustainability has become a central focus, with biodegradable and eco-friendly biomaterials offering solutions that reduce environmental impacts while maintaining efficacy in medical applications. Innovations, such as microbial-derived polymers, plant-based materials and energy-efficient production methods, demonstrate the field's alignment with global sustainability objectives. Biomaterials' ability to tailor mechanical and physical properties for specific applications, from bone implants to drug delivery systems, has expanded their functionality, improving reliability and durability. Advances in surface engineering have further optimized cell adhesion and integration, ensuring biomaterials perform effectively in clinical settings. The global biomaterials market continues to grow rapidly, fueled by increasing healthcare demands, technological innovation and the rising prevalence of chronic diseases. This growth underscores the transformative potential of biomaterials to redefine medical treatments and enhance quality of life. As interdisciplinary research progresses, addressing challenges related to cost, safety and regulation will ensure that biomaterials continue to shape a healthier, more sustainable future for humanity.
Keywords: Biomaterials; biocompatibility; sustainability; nanotechnology; tissue engineering